Assessment on awareness and perception of forest offences in Hulu Perak, Malaysia - Baharom, Nor Azmi (2019)
The have been several studies conducted on the effects of deforestation, logging and shifting cultivation on Malaysia’s forest and yet little has been done on illegal encroachment aspects. Therefore, the objectives of this study were to assess the awareness on forest offences that has been practised, issues and challenges faced by authorities in enforcing the forest law and respondents’ perceptions towards authorities’ role to prevent forest offences. This study was conducted in Hulu Perak, Perak which among one of the states in Peninsular Malaysia with the highest forest reserve and encroachment activities. Sampling procedure consisted of two different groups. The first group is people in village and second group consist of officials from related governmental agencies who are directly or indirectly involved in the administration and enforcement of Permanent Reserve Forest (PRF). As for the research, pre-testing was done on 20 civilian people and 20 government officers from Forest Department Peninsular Malaysia Headquarter prior to the actual data collection. There were a total of 400 respondents' welcome to the response and complete the studies. A reliability analysis has been conducted and the analysis result has shown that all sections in the research instrument are good and have a high internal consistency. Result indicated that 88% of the people in Hulu Perak have Awareness and Perception of Forest Offences. Although the people are moderately knowledge about forest offences and it will not guarantee they will compliance on law. Evidently majority of them do not feel wrong to engage in such practice. This can be associated with their opinion and strong values that justify on encroachment or other offences and have been assimilated within the communities and families for a long time. Values take more time to be changed as it involved prolong instillation of ideas, thus a systematic ways of mind conditioning is perceived to be useful to change their values. In this respect, law enforcement is unlikely the only solution, the authorities must also emphasized on the need to incorporate educational element in their campaign or information drive.